How do patients describe their disabilities? A coding system for categorizing patients' descriptions. Issue 2 (April 2018) - Morris, Megan A.; Inselman, Jonathan; Rogers, Julie M.G.; Halverson, Colin; Branda, Megan; Griffin, Joan M.
Abstract: Background: To provide care that meets the values and preferences of patients with disabilities, health care providers need to understand patients' perceptions and understanding of their disability. No studies have explored patients' definitions of disability within the healthcare setting. Objective: The aim of the study was to understand how patients' define their disability in the healthcare setting and to develop a coding system for categorizing how they describe their disability. Methods: In 2000 all new outpatients at Mayo Clinic, Rochester, MN completed a form that inquired if they had a disability and if so, to write in the disability. The research team categorized the responses by disability type (e.g.: visual or physical) and how the patient described his disability or "disability narrative" (e.g.: diagnosis or activity). Results: Within 128, 636 patients, 14, 908 reported a disability. For adults, lower limb (26%) and chronic conditions (24%) were the most frequent disability type and activity limitations (56%) were the most frequent disability narrative category. For pediatric patients, developmental disabilities (43%) were the most frequently reported disability type and diagnoses (83%) were the most frequent disability narrative category. Patients used different disability narrative categories to describe different disability types. For example, most adults reporting a mental health listed a diagnosis (97%), compared to only 13% of those with lower limb disabilities. Conclusions: Patients had diverse descriptions of their disabilities. In order for providers and healthcare organizations to provide high-quality care, they should engage patients in developing a consistent, patient-centered language around disability.